Overlapping Structural and Functional Brain Changes in Patients With Long‐Term Exposure to Fibromyalgia Pain. Issue 12 (27th November 2013) - Jensen, Karin B.; Srinivasan, Priti; Spaeth, Rosa; Tan, Ying; Kosek, Eva; Petzke, Frank; Carville, Serena; Fransson, Peter; Marcus, Hanke; Williams, Steven C. R.; Choy, Ernest; Vitton, Olivier; et al.
Abstract : Objective: There is vast evidence to support the presence of brain aberrations in patients with fibromyalgia (FM), and it is possible that central plasticity is critical for the transition from acute to chronic pain. The aim of the present study was to investigate the relationship between brain structure and function in patients with FM. Methods: Functional connectivity of the brain during application of intermittent pressure–pain stimuli and measures of brain structure were compared between 26 patients with FM and 13 age‐ and sex‐matched healthy controls. Magnetic resonance imaging (MRI) was performed to obtain high‐resolution anatomic images and functional MRI scans of the brain, which were used for measurements of pain‐evoked brain activity. Results: FM patients displayed a distinct overlap between decreased cortical thickness, decreased brain volumes, and decreased functional regional coherence in the rostral anterior cingulate cortex. The morphometric changes were more pronounced with longer exposure to FM pain. In addition, there was evidence of an association between structural and functional changes in the mesolimbic areas of the brain and the severity of comorbid depression symptoms in FM patients. Conclusion: The combined integration of structural and functional measures allowed for a unique characterization of the impact of FM pain on the brain. These data may lead to the identification of early structural and functional brain alterations in response to pain, which could be used to develop markers for predicting the development of FM and other pain disorders.